ANDROID PLATFORM OVERVIEW: M-LEARNING APPLICATION FOR COLLEGE EDUCATION - Kamal, Taufiq; Hamdan Irfan Wijaya; Andika Yuma Nuruz Zaman (Universitas Mulia, 2021)
On average, students of the Yogyakarta Nahdlatul Ulama University (UNU Yogyakarta) have difficulty accessing course materials and self-assessments from e-learning platforms without the internet. The author uses a qualitative method by using observation to get direct information about access to course material from the e-learning platform. The mobile learning (m-learning) application prototype was developed through the android platform using the Java programming language. As a result, the use of m-learning can be one of the best modules of mixed learning techniques. The author recommends that UNU Yogyakarta integrate it with their e-learning platform. This m-learning application intends to complement the e-learning system and make students whenever and wherever they want to gain knowledge without the internet via an android phone. Future researchers can connect the m-learning application and other aspects of the e-learning platform.